Kung-Fu - Kijowski, Janusz (Poland, 1980)
A well-regarded engineer in a big enterprise is hounded by trumped up attacks on his integrity when he delves too deeply into the way bonuses are handled by the management. He gets into an argument with the guard, is arrested and subsequently fired. An old friend, a journalist, tries to sort things out but the victim's stubbornness and past problems with his wife lead to losses on both sides.
Keywords: Fiction films